Enhanced Low-Temperature Hydrogen Storage in Nanoporous Ni-Based Alloy Supported LiBH4 - Chen, Xi; Li, Zhao; Zhang, Yue; Liu, Dongming; Wang, Chunyang; Li, Yongtao; Si, Tingzhi; Zhang, Qingan (Frontiers in Chemistry, 2020)
To reveal the synergistic effect of nanoconfinement and metallic catalysis on the hydrogen storage properties of LiBH4, the nanoporous Ni-based alloy (np-Ni) was prepared herein by dealloying of the Mn70Ni30 alloy in (NH4)2SO4 solution, and then LiBH4 was loaded into np-Ni to construct the LiBH4/np-Ni hydrogen storage system using wet impregnation. It was found that dehydrogenation of the LiBH4/np-Ni (1:5) system starts at around 70 °C and ends before 400 °C, with approximately 11.9 wt.% of hydrogen desorbed. The apparent dehydrogenation activation energy for the LiBH4/np-Ni (1:5) system was remarkable decreased to about 11.4 kJ/mol. After rehydrogenation at 450 °C under 8 MPa hydrogen pressure, approximately 8.2 wt.% of hydrogen can be released from about 60 °C upon second dehydrogenation. These obtained results would provide an efficient strategy for improving the hydrogen storage properties of other metal borohydrides.